أهمية التدقيق الداخلي في تحسين نظام الرقابة الداخلية في المؤسسة الاقتصادية دراسة حالة المركب الصناعي التجاري الحضنة -المسيلة- - بوقرة خالد - خيراني أمين (جامعة المسيلة, 2020)
This study aimed to explain the various concepts related to the internal audit, internal control system in addition to determining the relationship between them, drawing on a range of theoretical study references (books, Articles, thesis And others), In the applied area, an exploratory field study was undertaken And use some search tools such as observation and interview. The most important results achieved Internal audit is a control function in the organization, It has a special place within the organizational structure of the institution, it is one of the tools on which enterprise management depends To achieve its goals, Especially in the commercial industrial complex on which the study is based, Internal audit contributes to improving the internal control system in the commercial industrial complex hodna -m'sila-, By carefully detecting existing errors and deviations and trying to identify the parties responsible for them, and Through our evaluation of the internal control system, And make some improvements and suggestions that would elevate the commercial industrial complex